The Review of Social Studies Curriculum as a Political Text In the Context of Neoliberalism - Fahrettin Korkmaz (Anı Publishing, 2017)
This study aims to examine the 6th grade Social Studies curriculum as a political text in the context of neoliberalism ideology from the perspective of re-conceptualization. For this purpose, the 6th grade Social Studies textbook, student workbook and teacher guidebook were used as data source. Document analysis method was used as the method of the study. The content analysis and critical discourse analysis methods were used in the analysis process of the data. The content analysis method was used in the process of creating themes and sub-themes while the critical discourse analysis was used in the interpretation of findings from the data sources. The themes of entrepreneurship, rights, responsibilities and freedoms, and corporate language in regard to the ideology of neoliberalism were reached by examining said data sources and literature. Sub-themes related to the theme were created and frequency values were determined. According to the obtained findings in the context of entrepreneurship, rights, responsibilities and freedoms, and corporate language themes related to the ideology of neoliberalism, it is concluded that the Social Studies Course (SSL) curriculum is influenced by the ideology of neoliberalism to a significant extent. Researchers can study on different ways of understanding the educational curriculum such as historical text, social gender and phenomenological understanding of the educational curriculum which are part of the re-conceptualization movement's types pf understanding the educational curriculum.